Simultaneous voltammetric determination of carbendazim and carbaryl in medicinal plant infusions with a boron-doped diamond electrode. Issue 8 (21st June 2017) - Lima, Thays de Souza; Simões, Fábio Ruiz; Codognoto, Lucia
ABSTRACT: This study is aimed to develop an electroanalytical methodology using a boron-doped diamond electrode to determine simultaneously and selectively carbendazim (CBZ) and carbaryl (CAR). In previous studies using cyclic voltammetry oxidation, peaks were observed at 1.03 V (CBZ) and 1.44 V (CAR), with characteristics of an irreversible process controlled by diffusion of species, with a supporting electrolyte of BR buffer (0.1 mol L −1 ) and pH adjusted to 6.0. The differences between the potentials for both pesticides, about 400 mV, indicate the possibility of selective determination of CBZ and CAR. The square-wave voltammetric parameters were optimised. The best separation conditions were pH 6.0, square-wave frequency of 100 s −1, pulse amplitude of 50 mV and scan increment of 2.0 mV. These parameters were used to obtain the calibration curves of CBZ and CAR. An analytical curve was constructed in the range concentration of CBZ of 1.3 mg L −1 to 15.3 mg L −1 and CAR of 1.0 mg L −1 to 11.4 mg L −1, respectively. The limits of detection (LOD) and limits of quantification (LOQ) for CBZ were 0.40 mg L −1 and 1.30 mg L −1, respectively. For CAR, the LOD and LOQ were 0.30 mg L −1 and 1.00 mg L −1, respectively. Sensitivity values were 0.78 and 2.60 µA/mg L −1 for CBZ and CAR, respectively. The electroanalytical method was applied in Mikania glomerata infusions. The recovery values were 106.2% and 116.5% for CBZ and CAR, respectively. The results show that the developed method is suitable for application in medicinal plant samples.